2005
DOI: 10.1073/pnas.0509822102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tyrosinase trafficking and processing by presenilins: Partial loss of function by familial Alzheimer's disease mutation

Abstract: ␥-secretase ͉ pigmentation ͉ melanocyte ͉ knock-out ͉ knock-in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…It is known to process a series of membrane receptors into signaling molecules that can thereafter translocate (35). In the RPE, it was known to take part in the trafficking and processing of tyrosinase enzymes, responsible for normal pigmentation (39). The data presented in our report provide evidence for the first time that PEDF inhibits VEGF-induced barrier breakdown of RPE cell monolayers through the activation of ␥-secretase.…”
Section: Discussionsupporting
confidence: 50%
“…It is known to process a series of membrane receptors into signaling molecules that can thereafter translocate (35). In the RPE, it was known to take part in the trafficking and processing of tyrosinase enzymes, responsible for normal pigmentation (39). The data presented in our report provide evidence for the first time that PEDF inhibits VEGF-induced barrier breakdown of RPE cell monolayers through the activation of ␥-secretase.…”
Section: Discussionsupporting
confidence: 50%
“…Another group has recently reported similar coat color changes in rats treated chronically with LY411,575 (Pagnozzi et al, 2004). This phenotype may be related to evidence that ␥-secretase inhibition reduces melanin synthesis, blocks melanosome pigmentation, and affects trafficking of tyrosinase (involved in the melanin synthesis pathway) (Wang et al, 2006) and that Notch is involved in cell fate determination of hair follicular stem cells (Yamamoto et al, 2003). These findings reflect a cautionary note that other side effects of chronic ␥-secretase inhibition may emerge with further testing.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, it is becoming increasingly clear that PS1 regulates the intracellular trafficking of several membrane proteins in neuronal and non-neuronal cells (Naruse et al, 1998;Capell et al, 2000;Annaert et al, 2001;Kim et al, 2001;Edbauer et al, 2002;Leem et al, 2002;Cai et al, 2003;Pigino et al, 2003;Wang et al, 2006). For example, expression of FAD-linked PS1 variants markedly impairs intracellular trafficking of membrane proteins in cellfree reconstitution systems (Cai et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies using cultured primary neurons suggest that PS1 plays a role in regulation of intracellular trafficking of selected proteins, including APP (Naruse et al, 1998;Capell et al, 2000;Kim et al, 2001;Cai et al, 2003), the neurotrophin receptor TrkB (Naruse et al, 1998), N-cadherin (Uemura et al, 2004), the PS1-interacting proteins intercellular adhesion molecule-5 (ICAM-5)/telencephalin (Annaert et al, 2001), and nicastrin (Edbauer et al, 2002;Leem et al, 2002), whereas PS2 has been shown to regulate the trafficking of cystatin C (Ghidoni et al, 2006). More recently, Wang et al (2006) have reported that, in the absence of PS1, the retinal pigment epithelium fails to undergo pigmentation because of mislocalization of 50 nm post-Golgi vesicles containing tyrosinase that would normally be transported to melanosomes. Finally, there is evidence that PS1 may play a role in the modulation of some protein kinase activities (Takashima et al, 1998;Pigino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%